Phosphoenolpyruvate carboxykinase 2-mediated metabolism promotes lung tumorigenesis by inhibiting mitochondrial-associated apoptotic cell death - Zhang, Jing; He, Wenjuan; Liu, Dongmei; Zhang, Wenyu; Qin, Huan; Zhang, Song; Cheng, Ailan; Li, Qiang; Wang, Feilong (Frontiers in Pharmacology, 2024)
Background: It is unknown how cancer cells override apoptosis and maintain progression under nutrition-deprived conditions within the tumor microenvironment. Phosphoenolpyruvate carboxykinase (PEPCK or PCK) catalyzes the first rate-limiting reaction in gluconeogenesis, which is an essential metabolic alteration that is required for the proliferation of cancer cells under glucose-limited conditions. However, if PCK-mediated gluconeogenesis affects apoptotic cell death of non small cell lung cancer (NSCLC) and its potential mechanisms remain unknown. Methods: RNA-seq, Western blot and RT-PCR were performed in A549 cell lines cultured in medium containing low or high concentrations of glucose (1mM vs 20mM) to gain insight into how cancer cells rewire their metabolism under glucose-restriction conditions. Stable isotope tracing metabolomics technology (LC-MS) was employed to allow precise quantification of metabolic fluxes of the TCA cycle regulated by PCK2. Flow Cytometry was used to assess the rates of early and later apoptosis and mitochondrial ROS in NSCLC cells. Transwell assays and luciferase-based in vivo imaging were used to determine the role of PCK2 in migration and invasion of NSCLC cells. Xenotransplants on BALB/c nude mice to evaluate the effects of PCK2 on tumor growth in vivo. Western blot, Immunohistochemistry and TUNEL assays to evaluate the protein levels of mitochondrial apoptosis.Results: This study report that the mitochondrial resident PCK (PCK2) is upregulated in dependent of endoplasmic reticulum stress-induced expression of activating transcription factor 4 (ATF4) upon glucose deprivation in NSCLC cells. Further, the study finds that PCK2-mediated metabolism is required to decrease the burden of the TCA cycles and oxidative phosphorylation as well as the production of mitochondrial reactive oxygen species. These metabolic alterations in turn reduce the activation of Caspase9-Caspase3-PARP signal pathway which drives apoptotic cell death. Importantly, silencing PCK2 increases apoptosis of NSCLC cells under low glucose condition and inhibits tumor growth both in vitro and in vivo.In summary, PCK2-mediated metabolism is an important metabolic adaptation for NSCLC cells to acquire resistance to apoptosis under glucose deprivation.